Correlative Assessment of Blood Parameters and Periodontal Status in Smokers- A Pilot Project: Life Sciences-Periodontitis for Dental Health - Dr Shreya Shetty; Dr Mawadah Almehmadi; Dr Halah Qadah; Dr Mazen Ismael Zaafrani; Dr Shrooq Osama Ezzaddin; Dr Jumanah Khaled Alsaedi; Khamrunissa Hussain Sheikh (International Journal of Life Science and Pharma Research, 2022)
Platelets and leukocytes activated in response to periodontal microorganisms during bacteremia can go on to excite other cells, enhancing the likelihood of atherosclerosis and coronary artery disease. Reports also indicate that decrease in the number of erythrocytes may occur secondary to periodontal disease. Smoking is a known risk factor for periodontal disease by virtue of its adverse effects on the blood cells. It was therefore decided to investigate the relationship between the red blood cel l(RBC), white blood cell (WBC) and platelet counts and periodontal parameters among smokers and non- smokers; to subsequently assess any implication of the systemic effects. Blood counts(RBC, WBC, platelets) for the present study were obtained from peripheral venous blood of 126 patients , both male and female aged between 18-45 years, in each group as follows: GROUP 1 :Periodontally healthy (n = 42) (non-smokers) GROUP 2: Chronic periodontitis (n = 42)( non- smokers) GROUP 3: Chronic periodontitis (n = 42) ( smokers) The clinical parameters to assess periodontitis included plaque index(PI), bleeding index(BI) and Clinical Attachment Loss( CAL) and history of smoking was elicited based on amount, frequency and duration of smoking. ANOVA tests followed by post HOC –Tukey HSD test revealed that there were significant differences between the 3 groups with respect to PI, BI and RBC counts(p<0.05). Pearson correlation test revealed a significant correlation between plaque index and platelet counts in group 1 only(p<0.05). Additionally, a significant correlation was also observed between WBC and platelet counts in all three groups(p<0.05).Variations in blood counts in different periodontal situations may pose a risk of systemic inflammation in smokers and non- smokers.